The Role of Informal Security in Combating Insecurity in New Kutunku Gwagwalada Area Council, Federal Capital Territory (FCT), Nigeria (Abuja Journal of Sociological Studies, 2026)
Insecurity remains a defining challenge across Nigeria, particularly in peri-urban areas where formal policing capacity is limited. This study examined how community-based security arrangements contribute to local safety and governance in New KutunkuGwagwalada town. The work is anchored on the Hybrid Governance and Collective Efficacy frameworks, the research explored how informal actors such as vigilante groups, youth associations, and neighborhood watch committees fill security gaps, maintain order, and mediate conflicts within the community. The study employed a mixed-methods design, combining household questionnaires, key informant interviews (KIIs), and focus group discussions (FGDs). Quantitative data were analyzed using descriptive statistics (frequencies and percentages), while qualitative data were subjected to thematic analysis. Findings revealed that over 72% of respondents perceived informal security groups as essential in reducing crime and supplementing the police. However, issues such as inadequate training, limited coordination with formal authorities, and occasional human rights violations were identified. KIIs and FGDs further highlighted that collective trust, social cohesion, and local accountability mechanisms significantly enhanced informal security effectiveness. The study concludes that informal security structures play a crucial complementary role in maintaining peace and safety in New Kutunku. It recommends institutionalized collaboration between local vigilantes and formal police, capacity-building on human rights, and legal frameworks that recognize but regulate informal actors. The research contributes empirically to debates on hybrid security governance and community-driven safety in contemporary Nigeria.